Zenana : everyday peace in a Karachi apartment building - Ring, Laura A., 1968- (Indiana University Press, 2006)
Presenting an ethnographic study of a multi-ethnic, middle-class high-rise apartment building in Karachi, Pakistan, this book argues that peace is the product of a relentless daily labour, much of it carried out in the zenana, or women's space. It provides a glimpse into contemporary urban life in a Muslim society.